Klaus von Beyme: Pioneer in the study of political theory and comparative politics - Beyme, Klaus von (Springer International Publishing Imprint: Springer, 2014)
Klaus von Beyme, a highly distinguished German political scientist, has been recognised as a “Pioneer in the Study of Political Theory and Comparative Politics”. When he received the highly esteemed Mattei Dogan Award during the XXII World Congress of Political Science in Madrid on 12 July 2012, in his laudatio Rainer Eisfeld portrayed Klaus v. Beyme as a “Global Scholar and Public Intellectual”. On the occasion of Klaus v. Beyme’s 80th birthday this book offers a selection of his major previously published and new texts focusing on “Empirical Political Theory”, “The Evolution of Comparative Politics, Revival of Normative Political Theory in Empirical Research”, “Theodor W. Adorno - Political Theory as Theory of Aesthetics”, “Historical Forerunners of Policy Studies”, “Political Institutions - Old and New”, “Representative Democracy and the Populist Temptation”, “Political Advisors to Politicians”, and on “The Concept of Political Class: A New Dimension of Research on Elites?”
Includes bibliographical references